2017
DOI: 10.3892/etm.2017.5334
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of CCR7(lo)PD‑1(hi) CXCR5+ CD4+ T cells, and associated factors Bcl‑6, CXCR5, IL‑21 and IL‑6 contribute to repeated implantation failure

Abstract: In vitro fertilization-embryo transfer (IVF-ET) can be used by infertile couples to assist with reproduction; however, failure of the embryo to implant into the endometrial lining results in failure of the IVF treatment. The present study investigated the expression of chemokine receptor 7 (CCR7)(lo) programmed death-1(PD-1)(hi) chemokine receptor type 5 (CXCR5)+ cluster of differentiation 4 (CD4)+ T cells and associated factors in patients with repeated implantation failure (RIF). A total of 30 females with R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Th17 cells can cause autoimmunity and inflammation, however which can be suppressed by Th17 cells to thus attain immune homeostasis [ 12 ]. Interleukin (IL)-6 or IL-21 facilitates differentiation of CD4 + T cells into Treg cells, whereas CD4 + T differentiates into Treg cells without IL-6 or IL-21 [ 13 , 14 ]. Th17 cells are found to generate proinflammatory cytokines like IL-17, IL-22, and IL-23 to aggravate inflammation and recruit neutrophils at the site of infection [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Th17 cells can cause autoimmunity and inflammation, however which can be suppressed by Th17 cells to thus attain immune homeostasis [ 12 ]. Interleukin (IL)-6 or IL-21 facilitates differentiation of CD4 + T cells into Treg cells, whereas CD4 + T differentiates into Treg cells without IL-6 or IL-21 [ 13 , 14 ]. Th17 cells are found to generate proinflammatory cytokines like IL-17, IL-22, and IL-23 to aggravate inflammation and recruit neutrophils at the site of infection [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the CCR7 and PD-1 expression on the cell surface, two major subsets were clearly identified within the circulating CXCR5 + CD4 + T cells. A study in repeated implantation failure reported the proportion of CCR7 lo PD-1 hi CXCR5 + CD4 + T cells was positively correlated with IL-21[ 31 ]. Another study found IL-21 was positively correlated with CCR7 lo PD-1 hi Tfh subset in transitional phase of Cystic echinococcosis[ 25 ].IL-21 is the main cytokine secreted by Tfh cells, reported as a critical immunomodulatory cytokine with various effects on all populations of lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…B-cell lymphoma 6 protein (BCL-6) was first identified as an oncogene important for proliferation in B-cell lymphomas but was later found in various tumors, as well as endometrial pathologies. Several recent studies have investigated the relationship between the expression rate of BCL-6 in the endometrial gland epithelium and endometriosis [5,[20][21][22][23]. Increased BCL-6 expression has been shown in UI and recurrent IVF failures [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have investigated the relationship between the expression rate of BCL-6 in the endometrial gland epithelium and endometriosis [5,[20][21][22][23]. Increased BCL-6 expression has been shown in UI and recurrent IVF failures [21,22]. BCL-6 overexpression has been associated with increased cellular proliferation [24].…”
Section: Introductionmentioning
confidence: 99%